2022
DOI: 10.3390/jrfm15020085
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Nature of Stock Return Volatility in BRICS and G7 Markets

Abstract: Through globalization and financial market liberalization, the opening up of markets has increased cross-border investments as investors search for higher risk-adjusted returns. This ability to invest internationally has raised the attention given to emerging markets that offer higher risk-adjusted returns relative to developed markets. However, despite the growing importance of emerging markets, the literature on the nature of volatility in global markets is typified by generalizations of findings from develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 100 publications
(135 reference statements)
7
15
0
Order By: Relevance
“…For the cryptocurrency, the AR parameters remained significant, whilst for the JSE, the non-significance is retained. The mean and the alpha parameter of the JSE are insignificant, which agrees with the results of Muguto and Muzindutsi (2022) who also used the structural breaks, which did not change these parameters. Their research revealed a significant structural break for the variance equation.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…For the cryptocurrency, the AR parameters remained significant, whilst for the JSE, the non-significance is retained. The mean and the alpha parameter of the JSE are insignificant, which agrees with the results of Muguto and Muzindutsi (2022) who also used the structural breaks, which did not change these parameters. Their research revealed a significant structural break for the variance equation.…”
Section: Resultssupporting
confidence: 86%
“…Such findings may indicate the need for some form of cryptocurrency market regulation. The inefficiency also means that traditional asset pricing models such as the CAPM and APT will be inadequate to model returns in these markets (Muguto and Muzindutsi 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, not surprisingly the associated international academic literature on stock market volatility, in terms of econometric methods and predictors being considered, is massive to say the least, with a proper review being beyond the scope of this paper. We refer interested readers to the works of [3][4][5][6][7] for detailed discussions in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…This choice also led to a divergence in the findings of the study ( Clement et al, 2021 ). Therefore, to uncover the “black box” formed by the organizational resilience of new ventures in the context of Localization in China, it is necessary to consider the characteristics of local culture ( Arikan et al, 2020 ) and interpret the mediating and moderating effects from a new perspective ( Muguto and Muzindutsi, 2022 ). Considering the long-standing problems of culture and economy ( Niedermeyer et al, 2020 ), Weber’s debates on culture and economic ethics, new institutional economics ( Carnevali et al, 2021 ), and informal institution theory ( Fricke et al, 2022 ) have made important contributions to studying the relationship between culture and economy ( Clark and Sourdin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%